Information, Direct Access to Farmers, and Rural Market Performance in Central India - Goyal, Aparajita (2012)
This paper estimates the impact of a change in procurement strategy of a private buyer in the central Indian state of Madhya Pradesh. Beginning in October 2000, Internet kiosks and warehouses were established that provide wholesale price information and an alternative marketing channel to soy farmers in the state. Using a new market-level dataset, the estimates suggest a significant increase in soy price after the introduction of kiosks, supporting the predictions of the theoretical model. Moreover, there is a robust increase in area under soy cultivation. The results point toward an improvement in the functioning of rural agricultural markets.